Społeczna percepcja badań doświadczalnych z udziałem pacjentów. Komunikat z badań dotyczących oddziaływania pola elektromagnetycznego na stymulator serca = Social perception of experimental studies involving patients. Results of the research on the impact of the emf field on a pacemaker - Pławiak-Mowna, Anna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The problems related to the impact of electromagnetic field (EMF) on biological environment and electromedical apparatus implanted in the human body (as the identification element of new risk factors) have been for decades the subject of research carried out by the scientists of various specialisations, both in Poland and abroad. We observe a great social request to present the data on impact of artificially generated electromagnetic fields (e.g. from the cellular telephony antennas) on the electro-implants used in medicine.
Keywords: badania doświadczalne; percepcja społeczna; pole elektromagnetyczne; stymulator serca